SOX5-Null Heterozygous Mutation in a Family with Adult-Onset Hyperkinesia and Behavioral Abnormalities - Michael Zech; Katharina Poustka; Sylvia Boesch; Riccardo Berutti; Tim M. Strom; Wolfgang Grisold; Werner Poewe; Juliane Winkelmann (Case Reports in Genetics)
SOX5 encodes a conserved transcription factor implicated in cell-fate decisions of the neural lineage. SOX5 haploinsufficiency induced by larger genomic deletions has been linked to a recognizable pediatric syndrome combining developmental delay with intellectual disability, mild dysmorphism, inadequate behavior, and variable additional features including motor disturbances. In contrast to SOX5-involving deletions, examples of pathogenic SOX5 small coding variations are sparse in the literature and have been described only in singular cases with phenotypic abnormalities akin to those seen in the SOX5 microdeletion syndrome. Here a novel SOX5 loss-of-function point mutation, c.13C>T (p.Arg5X), is reported, identified in the course of exome sequencing applied to the diagnosis of an unexplained adult-onset motor disorder. Aged 43 years, our female index patient demonstrated abrupt onset of mixed generalized hyperkinesia, with dystonic and choreiform movements being the most salient features. The movement disorder was accompanied by behavioral problems such as anxiety and mood instability. The mutation was found to be inherited to the patient’s son who manifested abnormal behavior including diminished social functioning, paranoid ideation, and anxiety since adolescence. Our results expand the compendium of SOX5 damaging single-nucleotide variation mutations and suggest that SOX5 haploinsufficiency might not be restrictively associated with childhood-onset syndromic disease.